Effects of a sucralfate-containing ointment on quality of life and symptoms associated with hemorrhoidal disease: patient-reported results of a Slovakian, pharmacist-led observational survey - Snopková, Miroslava; Sukel‘, Ondrej; Micanko, Jan (Frontiers in Gastroenterology, 2023)
Purpose: This pharmacist-led study evaluated the effect of a rectal ointment containing sucralfate on quality of life, symptom frequency and time to relief of symptoms in Slovakian individuals with hemorrhoidal disease (HD). Methods: The multicenter prospective survey was conducted at 45 community pharmacies in Slovakia. Pharmacists invited adults (≥18 years) using sucralfate-containing ointment for their HD-related symptoms to participate. Results: 241 patients completed the HEMO-FISS-QoL questionnaire and a survey of symptom frequency at the beginning and end of the 14-day survey period. The primary endpoint was the change in HEMO-FISS-QoL scores in patients with hemorrhoidal symptoms during the 7 days before the initial pharmacy visit. Of the 241 patients enrolled in the survey, 144 had experienced hemorrhoidal symptoms within the preceding 7 days (mean age 51 years; 59.0% female). For these 144 patients, the total HEMO-FISS-QoL score decreased (i.e., quality of life was improved) from baseline by a mean of –8.7 (95% confidence interval –12.6, –6.2; P<0.001) at day 14. The frequency of hemorrhoidal symptoms was significantly reduced (P<0.001 vs baseline). Symptom relief was rapid; at 1-hour post-treatment 54.6% of patients had relief from pain and 56.3% from itching, and by 24 hours post-treatment most patients had relief from these symptoms (77.2% and 73.0%, respectively). No incidents nor adverse events related to sucralfate-containing ointment were reported to pharmacists. Conclusions: The results of this pharmacist-led observational survey suggest that the sucralfate-containing ointment could improve quality of life in patients with HD, providing rapid relief with a good safety profile. To confirm these results in a larger, well-defined patient population, randomized controlled trials in patients with clinically diagnosed HD are warranted.